Sitotoksisitas terhadap Sel Leukemia L1210 dan Profil Kromatogram dari Serbuk Temu Putih Curcuma zedoaria (Berg) Rosc. yang Diradiasi - ERMIN KATRIN W.; JOHANS RICHARD ALBERT; SWASONO R. TAMAT; SUSANTO SUSANTO; HENDIG WINARNO (Fakultas Farmasi Universitas Pancasila, 2012)
White turmeric Curcuma zedoaria (Berg) Rosc. is useful for treating cancer disease. It is very susceptible to microbial, therefore gamma irradiation technique to reduce microbial contamination is necessary in order to extend the storing period. Gamma irradiation on white tumeric was carried out by cobalt-60 source at doses of 5, 7.5, 10, and 15 kGy. Then they gradually were maeerated with n-hexane, ethyl acetate, and ethanol. The purpose of this research was to study the effect of gamma irradiation by observing parameters on the cytotoxic activity of ethyl acetate extract and active fraction of white tumeric rhizome against L1210 leukemia cells, also profiles of thin layer and HPLC chromatograms of active fraction as anticancer agent. Ethyl acetate extract of irradiated and control samples were the most active to inhibit the growth of L1210 leukemia cells with IC50 value of 4.71 ug/mL. Ethyl acetate extracts from irradiated and control samples were fractionated using column chromatography and obtained 7 fractions (Fr), respectively. Fraction 3 of control sample was the most active fraction with IC50 values 1.43 µg/ ml. The IC50 value of Fr 3 decreased with increasing irradiation doses and chromatogram profiles of radiated samples with doses of > 5 kGy were changed. The maximum radiation dose for white turmeric preservation is 7.5 kGy, at this dose its anticancer efficacy was maintained.